Effect Of Concentration And Frequency Of Rice Washing Water Liquid Organic Fertiliser On Tomato Plant Growth And Yield - Laksamana Widodo; Tatik - Raisawati; Susi Handayani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose : The objective of this study was to evaluate the effect of various concentrations and application frequencies of liquid organic fertilizer (LOF) from rice washing water enriched with coconut water on the growth and productivity of tomato plants. Methodology : A factorial randomised complete block design was employed with three concentrations (1:5, 1:10, 1:15) and three fertilisation frequencies (two, three, and four applications). Growth and yield parameters such as plant height, leaf number, stem diameter, flowering age, fruit number, fruit diameter, and fruit weight were measured. Result : Results indicated that a 1:10 concentration significantly affected stem diameter and accelerated flowering, while four fertilisation applications yielded the fastest flowering. No significant interaction between the two factors was observed. Findings suggest that a 1:10 dilution combined with four applications provides the most favourable outcome for flowering. Novelty : The novelty of this research lies in the utilization of rice washing water, a household waste, enriched with coconut water as liquid organic fertilizer (LOF), along with the simultaneous evaluation of concentration and application frequency on the vegetative phase and tomato yield. Originality: The originality of this research is reflected in its environmentally friendly approach using locally available organic materials as an alternative to reduce reliance on chemical fertilizers in tomato cultivation. Conclusion : The study highlights rice washing water-based LOF as a sustainable alternative to enhance tomoto production. Type of Paper : Research article.